도시 수변 완충지역의 경관 계획에 관한 연구 - 탄성 (resilient) 관점의 계획 사례분석을 중심으로 - 양멍(Meng Yang); 홍관선(Kwan-Seon Hong) (한국콘텐츠학회 논문지, 20(7), 2020)
Flooding is an unavoidable natural disaster for the city. Flood disasters seriously undermine the city's economy, safety, and sustained development. In the course of development and construction of waterfront space in the same city, the construction of basic disaster prevention facilities cannot be avoided completely even if huge amounts of capital are invested to reduce the economic damage of flooding. The cost of rebuilding the city after the disaster is much higher than the cost of building disaster prevention facilities. In recent years, the theory of elasticity in urban reconstruction and so on has been a subject of city problem solving, creating widespread discussion and attention in academia. In other words, how to transform the concept of elasticity into practice based on theoretical and empirical factors is a real problem facing urban disaster. Through theoretical literature on the waterfront (space) buffer zone of a city (flood-weak area) and the case study of the city's practice, this paper tries to clarify the element of 5R, the theory of elastomeric fire prevention, and present detailed measures accordingly. In addition, the following two problems are addressed while emphasizing the feasibility of implementing the urban waterfront (space) plan of the elastomeric element around the urban water buffer zone. First, the means of disaster prevention planning are used to mitigate conflicts between individual utility of urban waterfront and disaster prevention functions in waterfront buffer zones, and second, the waterfront buffer zone can respond to flood-causing problems in terms of disaster prevention as much as possible through the elastic disaster prevention plan. 홍수는 도시가 피할 수 없는 자연재해이다. 홍수 재해는 도시의 경제와 안전, 그리고 지속발전을 심각하게 저해한다. 수변 공간에 대한 개발과 건설 과정에서 기본적인 방재시설의 건축을 통해 홍수의 경제적 피해를 줄이고자 막대한 자본을 투입하더라도 이를 완전히 피할 수는 없으며. 재해 발생 후 도시의 재건 비용은 방재(防災)시설의 건설비용보다 훨씬 많은 비용을 필요로 한다. 최근 몇 년간 도시재건 등에 있어 탄성(resilient)이론은 학계의 광범위한 토론과 주목을 불러일으키며 도시의 문제해결에 관한 주제가 되어왔다. 즉, 탄성의 방재개념을 이론과 경험적 요소를 토대로 어떻게 실천으로 전환시켜야 하는지가 도시방재가 마주하고 있는 현실적 문제이다. 본 논문은 도시의 수변(공간) 완충지역(홍수 취약지역)여 관한 이론 문헌과 도시의 실천 사례연구를 통해 탄성 방재이론인 5R 요소를 명확화하고, 이에 따른 상세 대책을 제시하고자 한다. 또한, 도시의 수변완충지역을 중심으로 탄성 방재이론 요소의 도시수변(공간)계획에서의 실행 가능성을 강조하는 동시에 다음과 같은 두 가지 문제를 해결하고자 한다. 첫째, 방재계획수단을 이용해 도시수변토지의 개별 효용과 수변완충지역의 방재기능 간의 갈등을 완화하는 것과 둘째, 수변완충지역이 탄성 방재계획을 통해 방재 측면에서 홍수가 수반하는 문제에 최대한 대응할 수 있게 하는 것이다.